Development and Optimization of Levobunolol Hydrochloride In-situ Gel for Glaucoma Treatment - Pandey, Ashish (International Journal of Pharmaceutical & Biological Archive, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The aim of present study was to develop and optimize Levobunolol HCl in-situ gels for glaucoma treatment. Levobunolol HCl ophthalmic solution has been shown to be effective in intraocular pressure (IOP) and may be used in patients with chronic open-angle glaucoma or ocular hypertension. Levobunolol HCl in-situ gel was prepared using various concentrations of polymers such as Carbopol-940 (0.1, 0.2, 0.3 and 0.4% w/v), HPMC- E50LV (0.5, 1.0, 1.5 and 2.0 % w/v) and HPMC E4M (0.2, 0.4 and 0.6 %w/v) by pH induced gelling system with an objectives of increasing contact time, achieving controlled release, reduction in frequency of administration and greater therapeutic efficacy of drug. The prepared in-situ gels were then evaluated for their visual appearance, clarity, pH, drug content analysis, in-vitro gellation (Gelling strength), rheological studies, in-vitro drug release studies and sterility testing. It is evident from these studies that, formed polymeric in-situ gels had transparent, clear possessing satisfactory gelling strength. The drug contents of all optimized formulations were found to be from 99.38 - 99.71%. Formulations of our in-situ gels may possess the characteristics of pseudoplstic fluid. Method used for sterility testing was found to be reliable. Results of this study revealed that, formulations (F21 and F24) containing Carbapol-940 (0.2 and 0.3%) and HPMC E4M (0.4%) released their drug contents, 95.55 % and 90 % respectively, when compared to formulations (F11 and F15) containing Carbapol-940 (0.3 and 0.4%) and HPMC E50LV (1.5%) over a period of 480 minutes.